The impact of cardiopulmonary exercise testing on patients over the age of 80 undergoing elective colorectal cancer surgery. (8th June 2016) - Chan, K. E.; Pathak, S.; Smart, N. J.; Batchelor, N.; Daniels, I. R.
Abstract: Aim: Advanced age and occult cardiorespiratory disease are associated with increased morbidity and mortality following surgery. Cardiopulmonary exercise testing (CPET) may allow the identification of high‐risk patients and facilitate planned postoperative critical care support. The aim of this study was to determine whether preoperative CPET in patients aged over 80 undergoing elective colorectal cancer resection was associated with improved outcome. Method: All patients aged 80 years and above undergoing elective colorectal cancer resection between 1 March 2011 and 1 September 2013 were retrospectively analysed. Referral for CPET testing was at the discretion of the operating surgeon. Postoperative critical care unit (CCU) admission was based upon the CPET results. Results: Ninety‐four patients were identified, of whom 48 underwent CPET testing. The CPET group were significantly older than the non‐CPET group (85 vs 83 years, P  = 0.04) and were more likely to have a planned admission to CCU postoperatively ( P  < 0.0001). Despite the increased use of CCU resources, the overall CCU length of stay (LOS) in the CPET group did not differ from the non‐CPET group, but the non‐CPET group had a higher proportion of Level‐3 care. There were no differences in the incidence of unplanned CCU admission between the CPET and the non‐CPET group ( P  = 0.23). There were no differences in overall LOS between the two groups ( P  = 0.42). There was no difference in mortality ( P  = 0.11), overall complications ( P  = 0.53) or severe complications ( P  = 0.3). Conclusion: Preoperative CPET testing in patients aged over 80 undergoing elective colorectal cancer resection allows identification of higher‐risk patients and mitigation of risk by preemptive admission to a CCU. This stratification allows equivalent results to be achieved in high‐ and low‐risk elderly patients undergoing colorectal surgery.